Associations of mucosal disaccharidase kinetics and expression in the jejunum of steers with divergent average daily gain. (29th August 2020) - Smith, Wyatt N; Brake, Derek W; Lindholm-Perry, Amanda K; Oliver, William T; Freetly, Harvey C; Foote, Andrew P
Abstract: The objective of this study was to quantify the differences in the activity of jejunal maltase and isomaltase between two groups of steers with average dry matter intake (DMI ) and differing average daily gain (ADG ). DMI and ADG were measured in crossbred steers ( n = 69; initial body weight = 456 ± 5.0 kg) consuming a finishing diet containing 67.8% dry-rolled corn, 20.0% wet distillers grains with solubles, 8.0% alfalfa hay, and 4.2% vitamin/mineral supplement on a dry matter basis for 84 d. Jejunal mucosal samples were collected from eight steers with the greatest (high) or least (low) ADG and average DMI (± 0.55 standard deviation). Homogenates of jejunal mucosa were incubated with increasing amounts of maltose and isomaltose to determine the disaccharidase kinetics. Total mucosal protein concentration (mg protein/g tissue; P = 0.45) of the mucosa and small intestinal weights ( P = 0.69) did not differ between the groups. Neither the Michaelis–Menten constant (Km ) of isomaltase ( P = 0.15) nor maltase ( P = 0.21) differed between groups. The isomaltase maximum velocity (V max ) expressed per gram of protein tended to differ ( P = 0.10) between groups of steers but did not differ ( P = 0.13) when expressed on a tissue basis. Similarly, neither the maltase Vmax expressed per gram of protein ( P = 0.31) nor tissue ( P = 0.32) differed between groups. While previous studies have indicated that disaccharidase expression is associated with differences in ADG, data presented here indicate that differences in enzyme activity at the end of the finishing period are minimal.